Legenda pro garmoshku - Andrey Filchenko; L.I.Kalinina; S.M.Milimov; Olga Potanina; Julia Kurganskaja (Andrey Filchenko, 2014)
Eastern Khanty, Vasyugan river, text recorded in 1992, by researcher A.A.Kim, from speaker Milimov S.M. born in approx. 1935 in Ozernoe village, speaker bi-lingual Khanty-Russian, education - middle school. Archived: Tomsk TSPU Field Archive. Volume Y-6. pp.129-133, 136. Manuscript scanned by Julia Kurganskaja in 2012; annotated and translated by Andrey Filchenko, Olga Potanina, Julia Kurganskaja, in 2013. Previously unpublished. Автор текста (рассказчик): Милимов Сидор Михайлович. Родился прим. в 1935 г. в Озерном. Образование среднее. Жил в Новом Васюгане. Автор записи (кем записано): А. А. Ким: Записано в 1992 г. в п. Н.Васюган, Томская область. Хранится: Архив ЯНС ТГПУ: Том У-6, стр. 129-133, 136. Манускрипт оцифрован каф. ЯНС: - сканирование: Курганская Ю.В., 2012 - набор, глосиирование и перевод: Фильченко А.Ю., Потанина О.С., Курганская Ю.В., 2013 Ранее не публиковался. Comprehensive Documentation & Analysis of two Endangered Siberian Languages: legacy data and last speakers of Eastern Khanty and Southern Selkup Eastern Khanty collector of Eastern Khanty narratives and local lore in 1960-1975 speaker of Eastern Khanty, Vasyugan river, recorded in 1992 by A.A.Kim